2015
DOI: 10.1080/07317115.2015.1032467
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Recruitment and Retention of Geriatric Participants With Hoarding Disorder

Abstract: This study describes the initial contact of 255 potential participants, recruitment of 63 participants, and retention of 57 participants from three geriatric Hoarding Disorder (HD) studies. Patients with HD were easily recruited from the community, primarily through the use of clinician referrals and posted flyers, as evidenced by steady patient flow despite lack of compensation for participation. Contrary to treatment outcomes of late life mood and anxiety disorders, geriatric HD patients are largely retained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The high retention rate of patients in both conditions throughout treatment and follow-up procedures demonstrates the motivation of HD patients in the community to engage in evidence-based treatment. The details of the techniques used to recruit and retain participants have been previously published 21 ; in brief, study staff utilized motivational interviewing and problem solving when scheduling participants in order to minimize potential barriers to treatment engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high retention rate of patients in both conditions throughout treatment and follow-up procedures demonstrates the motivation of HD patients in the community to engage in evidence-based treatment. The details of the techniques used to recruit and retain participants have been previously published 21 ; in brief, study staff utilized motivational interviewing and problem solving when scheduling participants in order to minimize potential barriers to treatment engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the recruitment methods and a discussion of the factors related to participant retention have been published elsewhere. 21…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, hoarding severity is often associated with premature dropout and poor treatment prognosis (Christensen & Greist, 2001;Mataix-Cols, Marks, Greist, Kobak, & Baer, 2002). Dropout rates for HD are at or above what is found in CBT trials for OCD (Ayers et al, 2015;Ong, Clyde, Bluett, Levin, & Twohig, 2016), yet research into what predicts treatment drop is scarce. In addition to attrition, more research is needed to understand the rates, correlates, and predictors of other types of treatment noncompliance in HD.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may keep many individuals with HD from seeking treatment altogether. Individuals with HD often only enter treatment because of external forces, such as a family member's insistence or civic pressure (Ayers et al, 2015;Frost, Steketee, & Williams, 2000). One HD study reported that only 3% of the older adults enrolled were self-referred for treatment services (Kim, Steketee, & Frost, 2001).…”
Section: Motivation and Readiness For Changementioning
confidence: 99%
See 1 more Smart Citation